Efeito da etapa supragengival na terapia periodontal: uma meta-análise de ensaios clínicos randomizados - Oliveira, Cícero Anghinoni de (2022)
Periodontitis is a chronic, multifactorial disease of an inflammatory nature, caused by a dysbiosis between the oral myrcobioma and the individual host response, clinically characterized by the destruction of dental support tissues. For its treatment, the academy recommends that first an initial approach of supragingival adjustment is carried out, which mainly aims at initial behavioral changes and, if necessary, the control of risk factors. Next, the second approach (related to the cause) is recommended, with professionally performed scaling and subgingival root planing. However, both stages can be delivered simultaneously by the professional, who will manage the patient's behavioral changes during the therapy process. To our knowledge, there is no systematic review that has evaluated randomized clinical trials comparing these two approaches. Therefore, the aim of this systematic review was to answer the following PICOS questions. Focused Question (QF) 1: Does non-surgical periodontal therapy (NSPT) when performed in different stages (1st stage: supragingival approach; second stage: subgingival approach) produce better resultsthan both stages performed simultaneously? QF2: What isthe effect of the supragingival step performed alone (supragingival step only) compared to full NSPT on clinical indicators and patient-centered outcomes? Medline electronic databases / PubMed, Embase, Web of Science, Lilacs and gray literature sources) were searched by randomized clinical trials until May 08, 2022, without language or date restrictions. After screening and eligibility steps, two studies were included for QF1 totaling 77 participants and for QF2 four studies were included, totaling 362 participants. Direct evidence metaanalyses were performed with random effects models. FQ1: No significant difference was found between performing NSPT in different steps or both steps simultaneously, regardless of the clinical indicator evaluated (mean probing depth (PD), clinical attachment level (CAL), mean proportion (%) of sites with bleeding to probing (BOP) or sites with PS ≥ 5 mm. FQ2: NSPT complete was significantly better compared to the supragingival step performed alone in relation to the improvement of mean PD and CAL indicators, proportion (%) from BOP and from sites with PS 4-6 mm PD > 6mm. There are no patient-centered outcomes comparing both approaches. These findings indicate that both stages (supra and subgingival) are necessary for the treatment of patients with periodontitis and that, so far, there is not enough evidence to indicate the superiority of one or another approach in NSPT. However, given the limited number of primary studies performed and low certainty of evidence, definitive conclusions cannot be drawn until further primary studies are conducted.